Comparative Analysis of Financial Performance of IDX-listed Property Companies Before and During COVID-19 - Syawa, Jemimma Sarah Salsabilla; Septiyanti, Ratna (Cita konsultindo, 2024)
This study examines the financial performance of property sector companies listed on the Indonesia Stock Exchange (IDX) before and during the COVID-19 pandemic. Using the Wilcoxon Signed-Ranks Test, the research evaluates changes in profitability (Gross Profit Margin), liquidity (Cash Ratio), leverage (Debt to Equity Ratio), dividend policy (Dividend Payout Ratio), and company size (Total Revenue). Findings reveal significant declines in profitability and liquidity, an increase in leverage, and no significant changes in dividend policy or company size during the pandemic. The study highlights the impact of the pandemic on key financial metrics and underscores the need for further research incorporating additional variables and broader samples to improve generalizability. Limitations include a focus on selected financial aspects and the prevalence of negative earnings among many companies.